The Representation of Inequality and Social Class in Bong Joon-Ho’s Film, Parasite (2019) and Its Impact on The Formation of Audience Perspectives and Thinking - Cikal Fazri Al Ghazali; Khaerudin Imawan (Indonesian Journal Publisher, 2026)
Parasite (2019) at the same time depicted as social representation alongside entertainment, provides an insight into a functioning society and visualizes social class and inequality similar to modern-day society through Bong Joom-Ho Essentially, the narrative structures, visual signs and inter-character relations that Parasite uses to construct representations of social class and inequality are examined. It also explores how such representations might affect people and their understanding of socially constructed realities. The study uses qualitative analytical method with Critical Discourse Analysis (CDA) as the main approach. It is supported by data collection techniques including in-depth interviews with viewers, analysis of reviews on the Letterboxd application, and examination of reviews from the CineCrib YouTube channel. This study finds that the film Parasite uses specific cinematic visuals and social symbols to present class inequality, and audiences accurately grasped its core critique of social systems, which verifies the effectiveness of the film’s class narrative.